Aplikasi Kandidat Pemindai untuk Diagnosis Gen Shiga like toxin-2 dari Escherichia coli O157:H7 (PROBE APLICATION TO DIAGNOSTIC PROGRAME OF SHIGA LIKE TOXIN-2 (STX2) GEN FROM ESCHERICHIA COLI O157:H7) - Suardana, I Wayan; Sujaya, I Nengah; Artama, Wayan Tunas (Jurnal Veteriner, 2013)
A Shiga-like toxin producing Escherichia coli O157:H7 has been detected in cattle fecal sample, atbeef, and human as well as in beef and indicating that the agent is a harmful zoonosis bacteria. Geneticanalysis of Shiga toxin Escherichia coli (STEC) gene is important for development of probe to improve thediagnosis method for the agent. The study consisted of degrading and synthezing of PS2 probe withnucleotide sequence, 5’TTACACATATATCAGTGCCCGGTGTGA-CAACGGTTTCCATGACAACGGACAGCAGTTATACCACTCTGCAACGTGTCGCAGCGCTGGAA-CGTTCCGGAATGCAAATCAGTCGTCA‘3, analyzing of labeled probe, extracting of genomic DNA, hybridizing dot-blot DNA-DNA, and finallydetecting of hybridization signal. The results show that PS2 probe can be used to detect Shiga like toxingene (stx2 gene) from E. coli O157:H7. The Probe has labeling efficiency up to 10 pg/?l. PS2 probe with 25ng/ml concentration has a capability to detect it’s complemantary in 10 ng/?l DNA samples concentration.
Keywords: E.coli O157:H7, Shiga like toxin, PS2 probe